Assessment of Teachers Content Knowledge and Its Effect on Teaching Financial Accounting in Some Selected Secondary Senior Schools in Lagos State - Aribisala Oluwadamilare Olufolarin; Adekola Ramon Abolore (PT FORMOSA CENDEKIA GLOBAL, 2023)
The study investigated assessment of teachers’ content knowledge and its effect on teaching Financial Accounting in some selected Secondary schools in Lagos State. Financial accounting goes beyond recording and keeping of business transactions. Teachers’ content knowledge is key in utilizing instructional materials in the most creative way, for reliably assessing students’ progress and for determining the most operative sequence for the subject’s presentation. The study adopted a descriptive research survey design. Three specific purposes and three research questions guided the study. The population consist of all Senior Secondary Schools in Shomolu Local Government Area of Lagos State, while three senior secondary schools were randomly selected for the study. A structured questionnaire was used for data collection which totaled 75 respondents. Based on the findings, it was concluded that teachers’ content knowledge affects student’s achievement in Financial Accounting. Recommendations were made that government bodies such as Ministry of Education and other agencies should organize workshops and conferences aimed at improving teacher content knowledge for enhancing better performances of student’s in Financial Accounting